The role of oxygen on the growth of palladium clusters synthesized by gas aggregation source. Issue 7 (2nd May 2019) - Chamorro‐Coral, William; Caillard, Amaël; Brault, Pascal; Andreazza, Pascal; Coutanceau, Christophe; Baranton, Stève
Abstract: Palladium clusters are grown using a gas aggregation source coupled to magnetron sputtering with oxygen as reactive gas. Clusters with a mean size between 2.6 and 3.3 nm are obtained. Oxygen enhances the deposition rate by a factor 3 (from 4 to 11 mg/h cm −2 ) at the expense of the formation of larger clusters and the modification of the cluster composition. An increase of the oxygen flow rate induces a transition from Pd to PdO, this transition is followed by the formation of 2D structural defects in the crystals as displayed by grazing incidence X‐ray diffraction and high resolution transmission electron microscopy micrographs. Oxygen interacts with both the target and the sputtered atoms, highlighting that the target oxidation could be considered as the key step that drives the cluster growth processes. Abstract : Palladium clusters obtained with a gas aggregation source. In our study, oxygen was used to promote the cluster production; however, the cluster composition has changes.